2018
DOI: 10.1021/acschembio.7b00817
|View full text |Cite
|
Sign up to set email alerts
|

Allostery, Recognition of Nascent Peptidoglycan, and Cross-linking of the Cell Wall by the Essential Penicillin-Binding Protein 2x of Streptococcus pneumoniae

Abstract: Transpeptidases, members of the penicillin-binding protein (PBP) families, catalyze cross-linking of the bacterial cell wall. This transformation is critical for the survival of bacteria, and it is the target of inhibition by β-lactam antibiotics. We report herein our structural insights into catalysis by the essential PBP2x of Streptococcus pneumoniae by disclosing a total of four X-ray structures, two computational models based on the crystal structures, and molecular-dynamics simulations. The X-ray structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
2
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 37 publications
4
43
0
Order By: Relevance
“…To investigate the inferred crystal structure location of S. pyogenes PBP2x mutations relative to the S. pneumoniae orthologue, S. pyogenes PBP2x sequence variations were plotted onto the S. pneumoniae PBP2x crystal structure bound to oxacillin (PDB: 5OIZ) (11). Sequence conservation as determined by the frequency (for S. pyogenes ) and percentage (for S. pneumoniae ) of variant amino acids compared to the consensus was rendered onto the PBP2x crystal structure using UCSF Chimera (12).…”
Section: Methodsmentioning
confidence: 99%
“…To investigate the inferred crystal structure location of S. pyogenes PBP2x mutations relative to the S. pneumoniae orthologue, S. pyogenes PBP2x sequence variations were plotted onto the S. pneumoniae PBP2x crystal structure bound to oxacillin (PDB: 5OIZ) (11). Sequence conservation as determined by the frequency (for S. pyogenes ) and percentage (for S. pneumoniae ) of variant amino acids compared to the consensus was rendered onto the PBP2x crystal structure using UCSF Chimera (12).…”
Section: Methodsmentioning
confidence: 99%
“…It is possible that the PASTA domains strengthen the interaction between DivIB and the transpeptidase domain, but alternatively the PASTA domains interact with another region of DivIB. Our results show that PASTA domains can have distinct functions in similar proteins – whereas the PASTA domains in S. pneumoniae clearly function to allosterically activate the transpeptidase activity of the protein (12), their function in B. subtilis PBP2B is to stabilize an important protein-protein interaction in the divisome.…”
Section: Discussionmentioning
confidence: 88%
“…In PBP2x, loss of the PASTA domains abolishes the binding of Bocillin-FL, a fluorescent penicillin derivative (11) and localization of PBP2x to the division site (9), suggesting that PASTA domains mediate the interaction with peptidoglycan. This was nicely illustrated recently by a series of crystal structures that revealed that the PBP2x PASTA domains form an allosteric binding site for a pentapeptide stem in a nascent peptidoglycan strand, which positions another peptide stem on the same strand in the active site so that it can be cross-linked (12). The allosteric binding site is formed at the interface of the two PASTA domains and the transpeptidase domain and comprises the entire first and part of the second PASTA domain.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…We discern simple insight and design our next experiment with attention to the singular rather than the plurality of Ockham's razor . The allosteric control of S. aureus PBP2a (and perhaps of other PBPs) may well be to synchronize loop opening of the active site with protein translocation, but this explanation is almost certainly an oversimplification. The narrative presented here conceptualizes a two‐dimensional pathway for the peptidoglycan construction and deconstruction by P. aeruginosa when the realities of both AmpR regulation and cell‐wall biosynthesis are multidimensional .…”
Section: Resultsmentioning
confidence: 99%